TRANSFORMAÇÃO MARTENSÍTICA INDUZIDA POR DEFORMAÇÃO EM AÇOS INOXIDÁVEIS AUSTENÍTICOS AISI 304 E AISI 316 DEFORMADOS POR DIFERENTES PROCESSOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
Stainless steels with properties which allow high conformability and satisfactory mechanical resistance due to phase transformations are becoming prominently active for industries and metallurgical research centers. Therefore, the phenomena related to the work hardening must be understood and mastered, once the strain has an extremely important function on the phase transformation of these materials. For the investigations, are conducted different kinds of strains on the stainless steels by filing, compression and cold rolling at 12%, 31%, 50%, 70%, 80% and 90% reduction levels. In order to compare the materials, are conducted the following technics: optical microscopy, EDS, EBSD, X ray diffraction, hardness measurements and ferritoscope. The high hardness presented by these as received materials is attributed to the fact that they were not annealed. Low rolled steels showed high transformation into ε-martensite, and high rolled levels (like 90%) showed high grain elongation and very high α’- martensite fractions. Filling and compression also showed high α’- martensite fractions for the AISI 304. However, the AISI 316 didn’t show a significant fraction of α’- martensite after the compression test. Therefore, the high hardness showed by AISI 316 steel after the compression test is certainly due to classic work hardening mechanisms, not due to a α’- martensite transformation, which depends on the Stacking Fault Energy (SFE).
Keywords: aços inoxidáveis austeníticos; laminação; limagem; compressão; austenita; martensita; austenitic stainless steels; rolling; filing; compression; austenite; martensite; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA